Exploring the challenges of Iranian government hospitals related to Covid-19 pandemic management: a qualitative content analysis research from the nurses perspective - Alireza Jabbari; Sahar Salahi; Marziye Hadian; Zahra khakdel; Elaheh Hosseini; Hojjat Sheikhbardsiri (BMC Nursing, 2022)
Abstract Background The COVID-19 pandemic poses a major threat to global public health. As a result, to prepare healthcare systems for this unprecedented threat, a coordinated worldwide response is required. This study aimed to explore the hospitals challenges related to covid-19 pandemic management from the iranian nurses perspective. Methods This study was conducted as a qualitative content analysis in Iran. Using the purposive sampling method, data were collected through in-depth individual interviews with 35 nurse personnel. Graneheim and Lundman’s conventional content analysis methods were used to analyze the data and for the trustworthiness of the data, this study used Lincoln and Guba’s recommendations. Results After multiple rounds of analyzing and summarizing the data and taking into consideration similarities and differences, 5 main categories and 14 subcategories created based on the results of data analysis and including1) Leadership and management 2) Service delivery management 3) Human resources management 4) Equipment and Supplies Management and 5) Economic resources management. Conclusion Identifying the most important challenges of nursing can play an important role in improving the management of COVID-19pandemic. The analysis of the challenges by managers at local, provincial and national levels can lead to the presentation of effective solutions to address these challenges and improve the pandemic management process in the country.